IMPACT OF THE COVID-19 VIRUS ON STOCK MARKET RETURN IN INDONESIA - Hanna Gifani; Irene Rini Demi Pangestuti (Jurnal Akuntansi dan Pajak, 2023)
The purpose of the study was to investigates whether contagious infectious disease affect stock market outcomes. This study uses panel data analysis to test the effect of the Covid-19 virus on the Indonesia stock market. The results indicate that both the daily growth in total confirmed cases and in total cases of death causes by Covid-19 virus have significant negative effects on stock retuns across all companies on Indonesia stock exchange.